Carving Self-Identity: Hopi Katsina Dolls as Contemporary Cultural Expression - Dunlop, Balazs Shanna (My University, 2004)
This dissertation examines self-identity as expressed through contemporary Hopi katsina doll carving, an enduring Pueblo tradition and innovative art form. Although katsina dolls are produced by all Pueblo groups, only the Hopi, and to a much lesser extent the Zuni. produce figures for commercial sale. Consequently, this research focuses specifically on contemporary commercial Hopi katsina doll carvings. Within this dissertation, contemporary Hopi carving is considered as a highly expressive vehicle of representation in which carvers act as creative agents of cultural ideology. Following recent transcultured arts models, I argue for a linkage between the art of katsina doll carving, both process and product, and Hopi self-identity, asserting that new trends in carving articulate contemporary concerns regarding cultural continuity, survival and self-determination in a modem world. In addition to exploring this thesis, my case study of commercial Hopi katsina doll carving also approaches several broader theoretical themes and pertinent issues, including discussions of: the processes of transcultural exchange and commodification embodied in acculturated art; the social agency of art consumers in the Western market; and, notions of authenticity and the social production of value associated with art objects.
Keywords: Anthropology; Anthropology